2020
DOI: 10.1021/acs.jpca.0c06321
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Reactions of Hydroxyl Radicals with Furan and Its Alkylated Derivatives 2-Methyl Furan and 2,5-Dimethyl Furan

Abstract: Furans are promising second generation biofuels with comparable energy densities to conventional fossil fuels. Combustion of furans is initiated and controlled to a large part by reactions with OH radicals, the kinetics of which are critical to understand the processes occurring under conditions relevant to low-temperature combustion. The reactions of OH radicals with furan (OH + F, R1), 2methyl furan (OH + 2-MF, R2), and 2,5-dimethyl furan (OH + 2,5-DMF, R3) have been studied in this work over the temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 44 publications
5
51
2
Order By: Relevance
“…In untreated dried red pepper powder the furan level was 4.58 ng/g. In the previous study, furan production was found to be temperature-dependent in hot coffee samples ( 28 ). The furan levels in the roasted red pepper samples also increased with increasing temperature and time conditions.…”
Section: Resultsmentioning
confidence: 89%
“…In untreated dried red pepper powder the furan level was 4.58 ng/g. In the previous study, furan production was found to be temperature-dependent in hot coffee samples ( 28 ). The furan levels in the roasted red pepper samples also increased with increasing temperature and time conditions.…”
Section: Resultsmentioning
confidence: 89%
“…A number of reference compounds were used for each VOC, chosen so that the reference rate was roughly within a factor of five of the expected unknown rate, and with an attempt to use different references that had both faster and slower NO 3 reaction rates than the VOC. Reaction rates of the reference compounds (Table 2) with NO 3 addition to the C2 carbon followed by O 2 addition to the C5 carbon (Berndt et al, 1996), analogous to the OH addition reaction (Bierbach et al, 1995;Mousavipour et al, 2009;Yuan et al, 2017;Whelan et al, 2020). However, some of the reference compounds used in the experiments will form such radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Furan type compounds are removed from the atmosphere by reaction with the major oxidants OH, NO 3 and O 3 . There have been a number of studies on the rates of reaction of furan type compounds with the dominant daytime oxidant, OH (Lee and Tang, 1982;Atkinson et al, 1983;Wine and Thompson, 1984;Bierbach et al, 1992Bierbach et al, , 1994Bierbach et al, , 1995Aschmann et al, 2011;Ausmeel et al, 2017;Whelan et al, 2020). However, there have been fewer studies on the rates of reaction of furan type compounds with the major night-time oxidant, NO 3 (Atkinson et al, 1985;Kind et al, 1996;Cabañas et al, 2004;Colmenar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…HO 2 could be generated in these experiments from the abstraction of an H atom by O 2 from a β-ONO 2 -RO radical with available H atoms. The initial NO 3 reaction with furans is not thought to form β-ONO 2 -RO 2 radicals, with NO 3 addition to the C 2 carbon followed by O 2 addition to the C 5 carbon (Berndt et al, 1997), analogous to the OH-addition reaction (Bierbach et al, 1995;Mousavipour et al, 2009;Yuan et al, 2017;Whelan et al, 2020). However, some of the reference compounds used in the experiments will form such radicals.…”
Section: Ln ([Vocmentioning
confidence: 99%
“…Furan-type compounds are removed from the atmosphere by reaction with the major oxidants OH, NO 3 , and O 3 . There have been a number of studies on the rates of reaction of furan-type compounds with the dominant daytime oxidant, OH (Lee and Tang, 1982;Atkinson et al, 1983;Wine and Thompson, 1984;Bierbach et al, 1992Bierbach et al, , 1994Bierbach et al, , 1995Aschmann et al, 2011;Ausmeel et al, 2017;Whelan et al, 2020). However, there have been fewer studies on the rates of reaction of furan-type compounds with the major nighttime oxidant, NO 3 (Atkinson et al, 1985;Kind et al, 1996;Cabañas et al, 2004;Colmenar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%